Malaria in Refugee Children Resettled to a Holoendemic Area of Sub-Saharan Africa. (31st May 2022) - Hauser, Manuela; Kabuya, Jean-Bertin B; Mantus, Molly; Kamavu, Luc K; Sichivula, James L; Matende, Wycliffe M; Fritschi, Nora; Shields, Timothy; Curriero, Frank; Kvit, Anton; Chongwe, Gershom; Moss, William J; et al.
Abstract: Background: Malaria is a leading cause of morbidity and mortality in refugee children in high-transmission parts of Africa. Characterizing the clinical features of malaria in refugees can inform approaches to reduce its burden. Methods: The study was conducted in a high-transmission region of northern Zambia hosting Congolese refugees. We analyzed surveillance data and hospital records of children with severe malaria from refugee and local sites using multivariable regression models and geospatial visualization. Results: Malaria prevalence in the refugee settlement was similar to the highest burden areas in the district, consistent with the local ecology and leading to frequent rapid diagnostic test stockouts. We identified 2197 children hospitalized for severe malaria during the refugee crisis in 2017 and 2018. Refugee children referred from a refugee transit center (n = 63) experienced similar in-hospital mortality to local children and presented with less advanced infection. However, refugee children from a permanent refugee settlement (n = 110) had more than double the mortality of local children ( P < .001), had lower referral rates, and presented more frequently with advanced infection and malnutrition. Distance from the hospital was an important mediator of the association between refugee status and mortality but did not account for all of the increased risk. Conclusions: Malaria outcomes were more favorable in refugee children referred from a highly outfitted refugee transit center than those referred later from a permanent refugee settlement. Refugee children experienced higher in-hospital malaria mortality due in part to delayed presentation and higher rates of malnutrition. Interventions tailored to the refugee context are required to ensure capacity for rapid diagnosis and referral to reduce malaria mortality. Abstract : Refugee children from Democratic Republic of the Congo resettled to an area of high Plasmodium falciparum endemicity in Zambia experienced a higher burden of malaria than their local counterparts, explained in part by delayed presentation to care and higher malnutrition.